Jejunal Atresia in Preterm, LBW with Clinical Diagnosis of Down Syndrome Undergoing PA Without NICU and Uneventful Recovery (East West Medical College Journal, 2024)
Jejunal atresia is a rare congenital obstruction of the small intestine that necessitates prompt surgical intervention. This paper describes the successful primary anastomosis procedure for jejunal atresia in an 8-month-old premature, preterm, low birth weight baby with a clinical diagnosis of Down syndrome. Interestingly, the patient recovered without incident and did not require support in the neonatal intensive care unit (NICU). In a setting with limited resources, this case demonstrates the viability of treating jejunal atresia with primary anastomosis and emphasizes the criticality of prompt surgical intervention and attentive postoperative care for the best possible results.EWMCJ Vol. 12, No. 1&2, January-July 2024: 104-106